The role of hidden curriculum in the formation of professional ethics in Iranian medical students: A qualitative study - Yahya Safari; Alireza Khatony; Ehsan Khodamoradi; Mansour Rezaei (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Professionalism and medical ethics are a vital quality for doctors, which has been taken into account seriously in recent years. Perception of the factors affecting professionalism may help develop more efficient approaches to promote this quality in medical education. This study was aimed to explain the role of hidden curriculum in the formation of professional ethics in Iranian medical students. MATERIALS AND METHODS: This qualitative study was performed on 15 medical interns of Kermanshah University of Medical Sciences in 2019, using grounded theory. Sampling was started by purposive sampling and continued through theoretical sampling until complete data saturation. Data collection and analysis were done simultaneously. Data were interpreted by a constant comparative method according to Strauss and Corbin's approach. RESULTS: The analysis of the participants' interviews and reduction of findings using common themes yielded one class and four categories as well as a number of concepts as the role of hidden curriculum in the formation of professional ethics in medical students. The categories included the role of modeling in the formation of professional ethics, role of education in the formation of professional ethics, role of environmental factors in the formation of professional ethics, and role of personal and inherent attributes in the formation of professional ethics. CONCLUSION: Curriculum developers and medical education authorities need to proceed in line with the findings of the present study to provide a proper learning environment, in which the modeling, learning, and teaching conditions and supportive environmental atmosphere are taken into account in accordance with the inherent and individual characteristics of the learners in order to guarantee the formation of professional ethics in medical students.